Direct bone marrow injection of human bone marrow-derived stromal cells into mouse femurs results in greater prostate cancer PC-3 cell proliferation, but not specifically proliferation within the injected femurs - Bianca Nowlan; Elizabeth D. Williams; Michael Robert Doran (BMC Cancer, 2022)
Abstract Background While prostate cancer (PCa) cells most often metastasize to bone in men, species-specific differences between human and mouse bone marrow mean that this pattern is not faithfully replicated in mice. Herein we evaluated the impact of partially humanizing mouse bone marrow with human bone marrow-derived stromal cells (BMSC, also known as "mesenchymal stem cells") on human PCa cell behaviour. Methods BMSC are key cellular constituents of marrow. We used intrafemoral injection to transplant 5 × 105 luciferase (Luc) and green fluorescence protein (GFP) expressing human BMSC (hBMSC-Luc/GFP) into the right femur of non-obese diabetic (NOD)-severe combined immunodeficiency (scid) interleukin (IL)-2γ−/− (NSG) mice. Two weeks later, 2.5 × 106 PC-3 prostate cancer cells expressing DsRed (PC-3-DsRed) were delivered into the mice via intracardiac injection. PC-3-DsRed cells were tracked over time using an In Vivo Imaging System (IVIS) live animal imaging system, X-ray and IVIS imaging performed on harvested organs, and PC-3 cell numbers in femurs quantified using flow cytometry and histology. Results Flow cytometry analysis revealed greater PC-3-DsRed cell numbers within femurs of the mice that received hBMSC-Luc/GFP. However, while there were overall greater PC-3-DsRed cell numbers in these animals, there were not more PC-3-DsRed in the femurs injected with hBMSC-Luc/GFP than in contralateral femurs. A similar proportion of mice in with or without hBMSC-Luc/GFP had bone lessions, but the absolute number of bone lesions was greater in mice that had received hBMSC-Luc/GFP. Conclusion PC-3-DsRed cells preferentially populated bones in mice that had received hBMSC-Luc/GFP, although PC-3-DsRed cells not specifically localize in the bone marrow cavity where hBMSC-Luc/GFP had been transplanted. hBMSC-Luc/GFP appear to modify mouse biology in a manner that supports PC-3-DsRed tumor development, rather than specifically influencing PC-3-DsRed cell homing. This study provides useful insights into the role of humanizing murine bone marrow with hBMSC to study human PCa cell biology.